PENERAPAN TEKNIK TWO STAY TWO STRAY DENGAN MEDIA KONKRET DALAM PENINGKATAN PEMBELAJARAN MATEMATIKA SISWA KELAS V SD NEGERI GADUNGREJO - Savitri, Isnaini (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The Application of Two Stay Two Stray Technique using Concrete Media in Improving Mathematics Learning for the Fifth Grade Students. The objectives of this research are to describe the steps on the application of Two Stay Two Stray technique using concrete media, to improve Mathematics learning, and to describe problems and solutions. Thisresearc his conducted within three cycles Subjects of there search were 24 students of the fifth grade of SD Negeri Gadungrejo.The results of this research showed that the application of Two Stay Two Stray technique using concrete media can improve Mathematics learning for the fifth  grade students. Keywords: two stay two stray, media concrete, Mathematics. Abstrak: Penerapan Teknik Two Stay Two Stray dengan Media Konkret dalam Peningkatan Pembelajaran Matematika Siswa Kelas V Sekolah Dasar. Penelitian ini bertujuan untuk mendeskripsikan langkah-langkah penerapan teknik Two Stay Two Stray dengan media konkret, meningkatkan pembelajaran Matematika, dan mendeskripsikan kendala serta solusinya. Penelitian dilaksanakan dalam tiga siklus. Subjek penelitian ini adalah siswa  kelas V SD Negeri Gadungrejo yang berjumlah 34 siswa. Hasil penelitian menunjukkan bahwa penerapan teknik Two Stay Two Stray dengan media konkret dapat meningkatkan pembelajaran Matematika siswa kelas V SD. Kata kunci: two stay two stray, media konkret, Matematika